Promoting Learner Autonomy Through Teacher-Student Partnership Assessment in an American High School: A Cycle of Action Research - Edgar Picón Jácome (Universidad Nacional de Colombia, 2012)
In this article I present some findings of an action research study intended to find out to what extent a teacher-student partnership in writing assessment could promote high school students' autonomy. The study was conducted in a U.S. school. Two main action strategies in the assessment process were the use of symbols as the form of feedback and the design of a rubric containing criteria negotiated with the students as the scoring method. Results showed that the students developed some autonomy reflected in three dimensions: ownership of their learning process, metacognition, and critical thinking, which positively influenced an enhancement of their writing skills in both English and Spanish. Likewise, the role of the teacher was found to be paramount to set appropriate conditions for the students' development of autonomy.